Multisensory contributions to affective touch - Spence, C (Elsevier, 2021)
Just as for any other sensory system, researchers have long wanted to discriminate between the sensory discriminative and hedonic aspects of tactile perception. Supporting such a distinction, researchers have, in recent decades, uncovered the existence of a dedicated system of receptors in the hairy skin (C-Tactile, CT, afferents) that appear to be preferentially tuned to pleasant stroking (i.e. caressing) touch. No matter what kind of touch one is talking about, though, it is important to recognize that human perception is fundamentally multisensory, meaning that what we feel, not to mention what we think about the experience, is modulated by the inputs that are available to the other senses. This review summarizes the latest evidence concerning these multisensory contributions to tactile perception focusing, in particular, on the case of affective touch. Given that CT afferents for pleasant touch are far more common in the hairy (as compared to the glabrous) skin, the question is further raised as to whether the relative contribution of the various senses to tactile perception may differ as a function of the skin site stimulated (i.e. glabrous versus hairy skin) or the kind of judgment (sensory-discriminative versus hedonic) that is being made.